Uncovering the Meaning of Accountability: Is the Village-Owned Enterprises (BUMDes) Accountable? - Putra, Novrialdi Budi; Rusliyawati, Rusliyawati; Damayanti, Fera; Ardimansyah, Ardimansyah (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
This study aimed to comprehend the implementation of the principles of accountability, transparency, and involvement in managing Village-Owned Enterprises (BUMDes). BUMDes must be accountable and transparent and prioritize community engagement since the initial capital for BUMDes derives from the Village Fund Allocation (ADD), frequently allocated from the State Budget (APBN). The study employed a Descriptive Qualitative and Phenomenological approach. The primary research data source was interviews with BUMDes management informants and secondary sources include BUMDes yearly financial statements, associated regulations, documentation, and other files. The study’s findings demonstrated that the participation of initial capital of BUMDes sourced from village funds, that BUMDes financial statements are regularly submitted to the local head, head of BPD, and the community, that BUMDes operational managers do not understand the accounting treatment of BUMDes financial statements based on Permendes No. 3 of 2021 due to limited competence, that expenditures in the form of social funds are recorded and reported in the BUMDes annual report. The accountability principle has been pursued; however, it requires to be improved. Ease of access to information is provided through village websites, village videotrons, and village information boards that explain the variety of village financial information. In addition, BPD as an internal supervisor conducts checks and supervision from the establishment, management, and accountability of BUMDes by AD/ART. The principle of transparency has been implemented in BUMDes management. Involve the community actively in the establishment and establishment of BUMDes through consensual deliberation to apply participatory principles.